Utility of blood parameters in predicting oesophageal varices in patients with liver cirrhosis - Cyrin Annie Cyriac; Geeta Achutha Panicker; Sojan George Kunnathuparambil; Steffin Mathai Kattoor (Journal of Clinical and Scientific Research)
Background: This study aimed to evaluate the utility of various blood parameters in predicting oesophageal varices in patients with cirrhosis of liver. Methods: In this retrospective study, laboratory parameters like platelet count, haemoglobin level, serum alanine aminotransferase (ALT) aspartatae aminotransferase (AST) creatinine, albumin, international normalised ratio (INR) and bilirubin were collected from the medical records of patients with cirrhosis who underwent endoscopy for variceal bleeding. The predictors of oesophageal varices from these indices were calculated. Results: One hundred and sixty five patients (mean age 57.5 ± 10.7 years; males) were studied. Sixty seven patients (40.6%) had no oesophageal varices. Of the patients with varices (n = 98), 41 (24.8%) had small and 57 (34.5%) had large varices. Compared with patients without oesophageal varices, those with varices had significantly elevated serum aspartate aminotransferase (P = 0.018), serum bilirubin (P = 0.0001) and significantly low serum albumin (P = 0.0001). Platelet count was < 200,000/mm3 in patients with small and < 100,000/mm3 in patients with large varices (P = 0.0001). Prothrombin time-INR (PT-INR) was higher in patients with small varices compared to those with large varices compared to those with small varices (P = 0.0001). Sensitivity and specificity for PT-INR (area under curve [AUC] = 0.823) were 86% and 74%, respectively, and for platelet counts were (AUC = 0.813) 83% and 64%, respectively. Conclusions: Univariate analysis showed serum bilirubin, serum albumin, haemoglobin, platelet count were statistically significant. However, PT-INR and platelet counts showed high sensitivity and specificity.